(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: Alveolar echinococcosis is caused by Echinococcus multilocularis, a parasite of zoonotic significance with a wide range of intermediate and final hosts, and the parasite survives successfully in diversified conditions. Plentiful studies have been done to study the genetic structure of the population of the parasite and the level of intimate kinship using mitochondrial (mt) DNA. The present study was conducted to investigate the population structure, genetic variation, and phylogenetic relationship of various isolates of E. multiocularis submitted to GenBank worldwide. Sequences of mt genes (mt-cytochrome c oxidase (cox1), mt-NADH dehydrogenase (nad1)) of E. multilocularis were analyzed to achieve the set goals. Materials and Methods: A total of 275 and 124 gene sequences of mt-cox1 and mt-nad1 belonging to E. multilocularis, respectively, were retrieved from the National Center for Biotechnology Information GenBank. The retrieved sequences were subjected to alignment with respective reference sequences using MEGA software. The PopArt software was used to establish median-joining networks, while DnaSp was used to calculate neutrality and diversity indices. MrBayes software was used to investigate the phylogenetic association between haplotypes based on Bayesian phylogeny. Results: Approximately 13 and 20 distinctive haplotypes of nad1 and cox1 genes, respectively, were observed in the present study. In both of the mt genes, diversity indices indicated low haplotype (mt-cox1 = 0.140; mt-nad1 = 0.374) and nucleotide (mt-cox1 = 0.00111; mt-nad1 = 0.00287) diversities. The values of Tajima’s D and Fu Fs for a population of both of the genes under study were found to be negative. Conclusion: This study is a maiden attempt to provide insights into the population structure and genetic variation of E. multilocularis on a global scale. However, it is suggested that to better understand the population structure and genetic diversity of E. multilocularis, more geographical locations and amplifications of full-length gene sequences should be considered, which could be helpful in widening the insights into the genetic diversity of E. multilocularis. Adv. Vet. Anim. Res., 11(2): 264-274, June 2024 http://doi.org/10.5455/javar.2024.k772